Asistensi Akuntansi Keuangan Desa Marga Mulya - Septian Bayu Kristanto (SULUH: Jurnal Abdimas, 2020)
The aim of this study is to identify problems related to management of the village fund and to provide a guidance of village fund management. This study is conducted in Marga Mulya village in Tanjung Kait, Tangerang. This study used observation and interview method. The result showed that the main problem related to village fund is the lack of knowledge of the village head in implementing financial management of village fund based on Regulation No. 113/2015. It is coupled with a lack of facilitators from Government officers to assist the management of the village fund. This study purposed a computerized system for implementing the financial report is the solution to overcome these obstacles. By using this computerized system, reporting village fund will be done quickly and the financial statements will also be more reliable than reporting manually.